2019
DOI: 10.1002/maco.201910792
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behaviour of 316L stainless steel manufactured by selective laser melting

Abstract: This work investigates the electrochemical behaviour of an AISI 316L stainless steel produced by selective laser melting (SLM) and compares its behaviour with that of wrought stainless steel with similar chemical composition. The SLM stainless steel specimens are tested in the as‐produced condition without stress relief or recrystallization heat treatments. The electrochemical tests are carried out in two electrolytes: 3.5 wt% NaCl solution with neutral pH and with pH of 1.8. At the macroscale, the microstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
73
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(90 citation statements)
references
References 27 publications
14
73
0
Order By: Relevance
“…Others have reported selective attack of Cr, Mo depleted cell interiors within pits after anodic polarization in neutral chloride solution. 19,54 Nakao and Nishimoto showed similar preferential attack of primary austenite-solidifying substructure for LSM 904L SS (UNS N08904) in ferric chloride. [55][56] Furthermore, they demonstrated that the pitting resistance (pitting potential and critical pitting temperature) of this same material in ferric chloride solution increased with decreasing levels of microsegregation of Ni and Cr in the solidification substructure, Figure 5.…”
Section: Solidification Substructurementioning
confidence: 90%
See 2 more Smart Citations
“…Others have reported selective attack of Cr, Mo depleted cell interiors within pits after anodic polarization in neutral chloride solution. 19,54 Nakao and Nishimoto showed similar preferential attack of primary austenite-solidifying substructure for LSM 904L SS (UNS N08904) in ferric chloride. [55][56] Furthermore, they demonstrated that the pitting resistance (pitting potential and critical pitting temperature) of this same material in ferric chloride solution increased with decreasing levels of microsegregation of Ni and Cr in the solidification substructure, Figure 5.…”
Section: Solidification Substructurementioning
confidence: 90%
“…Distribution of corrosion studies in terms of stainless steel alloy, process, and environment. [2][3][4][5][6][7]10,[18][19]27,29,37,[47][48][49][50][51][53][54]57,[68][69]76,[91][92][101][102][103][104][105]109,116,129,134,137,144,[146][147][148][149]153,178,[185][186][187][188][189][190][191][192][193][194]…”
Section: Additive Manufacturing Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the microstructure and mechanical properties of alloys made from AM techniques have been studied extensively, there is a lack of deeper understanding regarding their corrosion related properties. The key microscopic characteristics in AM that affect the corrosion properties remain controversial [3][4][5][6][7][8][9][10]. The findings of the limited relevant studies regarding the effects of various types of microstructures/defects are briefly discussed in the following.…”
Section: Introductionmentioning
confidence: 99%
“…The reason why stainless steel has good corrosion resistance is that the formation of a dense passivation film on the surface of the stainless steel during the corrosion process can prevent the corrosion from continuing. Moreover, the formation of the passivation film depends on the environmental factors where the material is to be placed and the chemical composition of the alloy material . Some researchers have found that the addition of Mo in stainless steel can accelerate the formation of passivation film and reduce the corrosion current density of the active region in neutral halide solutions .…”
Section: Introductionmentioning
confidence: 99%